Audit on the use of empirical antibiotics in pregnant women with presumed UTI and their correlation to MSU results. (16th November 2010) - Rohatgi, T; Nemcova, M; Calvert, S; Porter, S; Rogerson, L
Abstract : Background: Urinary tract infection (UTI) is one of the most frequently seen 'medical' complications in pregnancy. It is common to treat pregnant patients with empirical antibiotics before awaiting the results of culture, many of which subsequently show no evidence of infection. Aim: The authors looked at pregnant women treated with empirical antibiotics for a presumed UTI to try and establish whether certain symptoms and urine dipstick results were associated with a positive culture result. Method: This was a retrospective study on 100 pregnant women across three hospitals in UK (Leeds General Infirmary, Bradford Royal Infirmary and Airedale General Hospital). Results: The authors analysed data of 114 episodes of presumed UTI among 100 patients. Only 19% of patients demonstrated positive growth on microbiological cultures. Our study revealed that the combination of urinary symptoms and nitrite on dipstick had a high positive predictive value (26%) and specificity (82%) whereas it lacked in sensitivity (27%). Cefradine 500 mg four times daily for 5 days was the most common antibiotic used and 14% episodes grew bacteria that were resistant to Cefradine. Only 37% episodes had repeat mid-stream urine (MSU) sent. Conclusion: Empirical antibiotic treatment for presumed UTI in pregnancy will occasionally be needed especially when there is a combination of clinical suspicion and positive urinary dipstick testing (leucocytes or nitrite). However, any decision to treat should be revisited once MSU results are available as unnecessary treatment with antibiotics can leads to antimicrobial resistance.